PENGARUH LAYANAN INFORMASI TERHADAP PENINGKATAN PERILAKU ASERTIF SISWA KELAS X SMK LABOR BINAAN FKIP UNRI PEKANBARU - Siameka, Sera Siameka Sera; Umari, Tri Umari Tri; Asyari, Abu Asyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of information service increase assertiveness behavior in class X SMK LABOR BINAAN FKIP UNRI Pekanbaru. The method used was experimental method to pattern one-group pretest-posttest. To collect the data used random sampling technique. Population for this research are all of students of class X SMK LABOR BINAAN FKIP UNRI PEKANBARU whom having too low assertiveness behavior and 101 students of class X AP 1, X AP 2, and X AK 1 used as sample part of population with draw way. Before have information service all student’s assertiveness behavior competence in too low category. In the process of information service to improve progress in the assertiveness behavior in every meeting. This is evident from analysis the value of ttotal is greater than ttable with a significant level of 5% (6,89>2,000). Than Ho rejected and Ha accepted, which means there is a significant difference to the improvement of student’s assertivenees behavior before given and after the information services. Student’s assertiveness behavior is better after has information services than before information services. Information service gives positive effect improve to assertiveness behavior. Based on the hypothesis test results turned out a significant influence on information service increased improvement of assertiveness behavior by 52%.Key Words: Information Service, Assertiveness Behavior.